A Feasibility study on Kappel Furniture - Abarra, Geraldine; De Jesus, Eleanor; Katigbak, Cristel Marie (Diliman, Quezon City College of Engineering, 2002)
Kappel Furniture is a venture engaged in the production of paper-based furniture. It applies the Appropriate Paper-based Technology and utilizes recyclable materials as inputs. Its product line includes tables and chairs for both adult and kids. To establish the feasibility f the venture, the market is first established. From historical data, the demand and the supply for furniture are projected using Weighted Moving Average Technique. The potential estimate of the market is determined and a target market, which is middle income households in the National Capital Region, is chosen. The marketing strategy is developed and the needed budget estimated. With a promising market for the products, the process of producing Kappel Furniture is presented. Subsequently, input requirements which include raw material, equipment and tooling, and labor requirements are chosen from the evaluated alternatives. The production schedule is also planned based on the computed capacity of the company. A layout is designed and the costs of investment and operation of the plant is estimated. The total costs of starting the company including the fixed investments, working capital, and pre-operating expenses are presented. To be able to finance the needed expenses, funding sources are chosen. Considering the relevant taxes, these finances are projected in a pro-forma income statement, balance sheet, and cash flow. To further evaluate the financial soundness of the venture, tests as well as sensitivity analysis is performed. Results indicate that the project is financially sound.The project must also be assessed socially by looking at the benefits to the community, environment, and government. Quantitative and qualitative cost-benefit analysis is done, which showed that the benefits outweigh the factors. Since it has a potential market and is technically, financially and socially acceptable, the project is concluded to be feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Kappel Furniture; Participatory monitoring and evaluation (Project management); Cardboard furniture